Aspergillary bronchopneumonia: an unusual cause of atelectasis and asphyxia in a leukemic patient - Velloso, Elvira Deolinda Rodrigues Pereira; Martinez, Gracia Aparecida; Dorlhiac-Llacer, Pedro Enrique; Chamone, Dalton Alencar Fischer (São Paulo Medical Journal, 1994)
A 22-year-old man in his first relapse of T-acute lymphoblastic leukemia developed fever and a pulmonary infiltrate after 23 days of granulocytopenia. Although having been under amphotericin B for 10 days, productive purulent cough ensued, with right lobe atelectasis and acute ventilatory failure that resolved after the elimination of a thick gelatinous bronchial plug. Sputum cultures yielded Candida Albicans and Staphylococcus epidermidis, and microscopic examination of the sputum plug disclosed Aspergillus hyphae. The patient died 9 days after, of a disseminated Aspergillus infection, confirmed by necropsy.